2016
DOI: 10.1186/s13019-016-0466-3
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary outcomes after pericardial window surgery: impact of operative technique

Abstract: BackgroundThe optimal window procedure for drainage of a large pericardial effusion has yet to be established. The purpose of this study was to compare the outcomes associated with the subxiphoid and thoracotomy pericardial window techniques, with a focus on perioperative pain and effusion recurrence rates.MethodsA retrospective single-center observational study of all pericardial window operations was performed, with the incision based on surgeon preference. Perioperative data was recorded including time to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 12 publications
2
22
0
8
Order By: Relevance
“…Within surgical interventions to evacuate the fluid exists the subxiphoid and thoracotomy techniques. While some studies have suggested respiratory complications associated with the thoracotomy approach, both are generally accepted for removing fluid buildup [7].…”
Section: Discussionmentioning
confidence: 99%
“…Within surgical interventions to evacuate the fluid exists the subxiphoid and thoracotomy techniques. While some studies have suggested respiratory complications associated with the thoracotomy approach, both are generally accepted for removing fluid buildup [7].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the recurrence of the pericardial effusion in our patient, which is a known and common complication of pericardiocentesis, a subxiphoid pericardial window was made which offers a more definitive management. There are currently two techniques for pericardial windows, the subxiphoid such as in this case, which involves approaching the pericardium under the xiphoid process of the sternum, and the thoracotomy technique which comprises access to the pericardium through an incision in the left fifth intercostal space [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] However, paper have shown that exploratory thoracotomy may be more effective in preventing refractory pericardial effusion. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%